Peran Budaya Organisasi dalam Memoderasi Pengaruh Motivasi Kerja dan Komitmen Organisasi terhadap Organizational Citizenship Behavior - Lusiana Amri; Irwan Cahyadi; Ika Yuliana; Baiq Dinna Widiyasti; Febria Nurmelia Marlina (Sekolah Menengah Kejuruan (SMK) Pustek, 2026)
Organizational Citizenship Behavior (OCB) represents voluntary employee behavior that exceeds formal job requirements and plays an essential role in supporting organizational effectiveness, particularly in educational institutions. However, limited extra-role behavior among educators indicates that OCB is not always optimally developed. This study aims to examine the effect of work motivation and organizational commitment on OCB, with organizational culture as a moderating variable. The research was conducted at the Nurul Islam Islamic Boarding School Foundation, involving all 43 educators as respondents using a saturated sampling technique. A quantitative approach was employed, and data were collected through structured questionnaires measured on a five-point Likert scale. The analysis was performed using Structural Equation Modeling with Partial Least Squares (SEM-PLS) through SmartPLS 3.0. The results reveal that work motivation and organizational commitment have a positive and significant effect on OCB. Furthermore, organizational culture significantly strengthens the influence of both work motivation and organizational commitment on OCB. These findings indicate that a supportive organizational culture enhances the effectiveness of individual motivation and commitment in fostering extra-role behavior among educators. This study provides empirical evidence on the strategic role of organizational culture in strengthening OCB within educational organizations.